The Study of Amtsal Al-Qur’an: Explanation of Hypocritical Verses in QS. Surah Al-Baqarah 17-18 - Raihani Salma Amatullah; Mowafg Masuwd; Nabila Aulia Nursalma; Ela Sartika; Wahyudi (Jurnal test, 2024)
Amtsal Al-Qur’an is a branch of Ulumul Qur’an that is important to know. With Qur’anic Proverbs, knowledge of things that are vague will be clearly known. Therefore, this research aims to explain the concept of Qur’anic Proverbs with the study of Surah Al-Baqarah verses 17-18. The approach and method used in this research is descriptive-qualitative with literature study. Various data were collected from various relevant sources such as the Qur’an, books, and scientific articles. The validation process was carried out by discussing with lecturers. This research produces a concept of Qur’anic Proverbs which consists of the message contained in the Qur’an can be understood through the science of Qur’anic Proverbs, the existence of proverbs in the Qur’an can make a message can be conveyed well because of the parable that is easy to understand. The study of QS. Al-Baqarah verses 17-18 can be understood that the analogies in it function as a warning not to become hypocrites. The findings of this study explain that the concept of Amtsal Al-Qur’an in QS. Al-Baqarah verses 17-18 are indeed relevant to the concept of Qur’anic Proverbs that should be. So that indeed in understanding the message in the content of the Qur’an cannot be separated from the Qur’anic Proverbs as part of Ulumul Qur’an to reveal the real message so that it can enter the human heart to obey what is commanded and stay away from its prohibitions. The salvation of the world and the hereafter can be achieved. Further research can be done by examining the verses of Amtsal Al-Qur’an based on regional interpretations in order to enrich the treasures of science.